2018
DOI: 10.1007/s11064-018-2491-1
|View full text |Cite
|
Sign up to set email alerts
|

AMPA-Type Glutamate Receptor Conductance Changes and Plasticity: Still a Lot of Noise

Abstract: Twenty years ago, we reported from the Collingridge Lab that a single-channel conductance increase through α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type ionotropic glutamate receptors (AMPARs) could mediate one form of plasticity associated with long-term potentiation (LTP) in the hippocampus (Benke et al., Nature 395:793-797, 1998). Revealed through peak-scaled non-stationary fluctuation analysis (PS-NSFA, also known as noise analysis), this component of LTP could be exclusively mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 77 publications
(118 reference statements)
1
50
1
Order By: Relevance
“…Support for increased number of synaptic AMPA receptors during LTP primarily comes from biochemical measurements demonstrating the level of surface receptors increases following LTP and from microscopy experiments directly visualizing tagged AMPA receptors as they cluster at postsynaptic sites following LTP induction (Shi et al, 1999 ; Heynen et al, 2000 ; Broutman and Baudry, 2001 ; Lu et al, 2001 ). Functional studies using peak-scaled non-stationary fluctuation analysis to estimate changes in receptor number and conductance following LTP are also consistent with insertion of AMPA receptors into the postsynaptic density (PSD) during LTP (Benke and Traynelis, 2018 ). While there is general agreement that AMPA receptors are recruited to the postsynaptic plasma membrane (PM) following LTP, the source of these receptors remains controversial.…”
Section: Introductionmentioning
confidence: 65%
“…Support for increased number of synaptic AMPA receptors during LTP primarily comes from biochemical measurements demonstrating the level of surface receptors increases following LTP and from microscopy experiments directly visualizing tagged AMPA receptors as they cluster at postsynaptic sites following LTP induction (Shi et al, 1999 ; Heynen et al, 2000 ; Broutman and Baudry, 2001 ; Lu et al, 2001 ). Functional studies using peak-scaled non-stationary fluctuation analysis to estimate changes in receptor number and conductance following LTP are also consistent with insertion of AMPA receptors into the postsynaptic density (PSD) during LTP (Benke and Traynelis, 2018 ). While there is general agreement that AMPA receptors are recruited to the postsynaptic plasma membrane (PM) following LTP, the source of these receptors remains controversial.…”
Section: Introductionmentioning
confidence: 65%
“…The unitary conductance (γ) of AMPA receptors was estimated using NSFA according to 6 (see also [19][20][21] ). Whole-cell responses were carefully selected for analysis using WinWCP (University of Strathclyde, Glasgow) and Mini Analysis software on the basis of the following criteria: first, precise alignment of traces on the rise phase; second, no contamination by spontaneous or polysynaptic currents; third, complete decay from the peak EPSCs.…”
Section: Peak-scaled Non-stationary Fluctuation Analysis (Nsfa)mentioning
confidence: 99%
“…In the present study, we have tested the hypothesis that LTPγ is due to the insertion of CP-AMPARs in young adult rodents using two theta burst stimulation (TBS) induction protocols that differed only in the timing between episodes, and applied peak-scaled non-stationary fluctuation analysis (NSFA) [19][20][21] to estimate γ before and after the induction of LTP 6,15,[22][23][24][25] . We found that the compressed TBS protocol (cTBS -inter-episode interval of 10 s) resulted exclusively in LTPN, for which CaMKII was both necessary and sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have tested the hypothesis that LTP γ is due to the insertion of CP-AMPARs in young adult rodents using two theta burst stimulation (TBS) induction protocols that differed only in the timing between episodes, and applied peak-scaled non-stationary fluctuation analysis (NSFA) 19 21 to estimate γ before and after the induction of LTP 6 , 15 , 22 25 . We found that the compressed TBS protocol (cTBS – inter-episode interval of 10 s) resulted exclusively in LTP N , for which CaMKII was both necessary and sufficient.…”
Section: Introductionmentioning
confidence: 99%